Bridging a gap in care: An integrated public health and Certified Community Behavioral Health Clinic (CCBHC) model to increase access - Ebert, Christine (My University, 2025)
Integrated care in outpatient settings aims to address fragmentation between physical and behavioral health by coordinating services around the whole person. This Integrated Learning Experience (ILE) focused on the development and implementation of an integrated care model between Lawrence-Douglas County Public Health (LDCPH) and Bert Nash Community Mental Health Center (Bert Nash), a Certified Community Behavioral Health Clinic (CCBHC). Guided by the Comprehensive Health Integration (CHI) framework from the National Council for Mental Wellbeing, the project spanned nearly two years and moved deliberately from planning to implementation. During 2024, the work centered on leadership engagement, workflow development, and creation of the legal infrastructure necessary for integration. Biweekly leadership meetings maintained steady momentum and culminated in the execution of a Designated Collaborating Organization (DCO) Agreement and an Organized Health Care Arrangement (OHCA). These agreements formalized LDCPH’s role in providing defined outpatient primary care services on behalf of Bert Nash, established privacy and data-sharing standards compliant with the Health Insurance Portability and Accountability Act (HIPAA) and 42 Code of Federal Regulations (CFR) Part 2, and clarified billing and compensation methodologies to support sustainability. The transition to implementation began on January 1, 2025, when LDCPH started seeing Bert Nash clients under the DCO framework. Co-location of Bert Nash staff at LDCPH facilitated warm handoffs, and LDCPH gained view-only access to the Bert Nash electronic health record (EHR), enabling better care coordination. Monthly updates to the LDCPH Health Board, ongoing leadership meetings, and the launch of an EHR/billing workgroup supported oversight and continuous quality improvement (CQI). By summer 2025, integration had extended to the front lines through twice-monthly provider meetings, the development of standard operating procedures (SOPs), creation of text macros and order sets, and additional provider training. Early clinical outcomes underscore the model’s potential. Clients disconnected from primary care were re-engaged and diagnosed with unmanaged hypertension, which was successfully treated and stabilized through structured follow-up. Registered dietitian consultations led to weight management successes, with improvements in nutrition and energy that supported overall treatment engagement. A psychiatric nurse practitioner provided street medicine in shelters and field settings, meeting clients where they were and reducing barriers to care access. These examples demonstrate how integration can improve outcomes for high need populations while aligning with public health goals of prevention, equity, and whole-person care. Challenges remain in harmonizing separate EHR systems, sustaining workforce capacity, and navigating cultural differences between public health and behavioral health practice. However, the governance structure (monthly high-level meetings, twice-monthly provider forums, and workgroups dedicated to referrals and billing) provides reliable mechanisms for addressing obstacles. Financial sustainability is supported by a blended capitation and per-visit reimbursement model, with rebasing scheduled in 2026 to align with service demand. This project illustrates how public health and behavioral health organizations can operationalize integration through deliberate planning, legal frameworks, and practical clinical tools. It demonstrates that integration is not simply a policy aspiration but a functional model capable of producing measurable health improvements. Future directions include formalizing nutrition integration, expanding linkages with family support and the Special Supplemental Program for Women, Infants, and Children (WIC) programs, exploring an embedded primary care panel at LDCPH, and assessing the feasibility of pursuing Federally Qualified Health Center (FQHC) Look-Alike status. Together, these efforts represent a sustainable path to advancing population health and equity through integrated care.
Keywords: integrated care; certified community behavioral health clinic CCBHC; primary care integration; Comprehensive Health Integration CHI; chronic care management